2020
DOI: 10.1002/cae.22304
|View full text |Cite
|
Sign up to set email alerts
|

The effects of game‐based learning in the acquisition of “soft skills” on undergraduate software engineering courses: A systematic literature review

Abstract: The software industry is becoming an increasingly important part of the economy in countries that have realized that the education of future software engineers is crucial to having a vibrant software industry. However, software engineering education is still influenced by traditional teaching impeding the acquisition of soft skills. Game‐based learning (GBL) combines learning with different known resources, such as games, to support and improve the teaching/learning process and/or student evaluation through ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 125 publications
(117 reference statements)
0
21
0
4
Order By: Relevance
“…In this research, 16 relatively high-quality research reviews in the last 5 years have been searched from the major databases in this field (Web of Science, EBSCO ERIC (Education Resources Information Center), IEEE Xplore and SpringerLink). After reviewing these papers, it is found that their main concerns can be summarized into the following four aspects: the effectiveness of GBL ( Meredith, 2016 ; Byun and Joung, 2018 ; Hussein et al, 2019 ; Pellas et al, 2019 ; Tokac et al, 2019 ; Chen et al, 2020 ; Garcia et al, 2020 ; Karakoç et al, 2020 ; Stančin et al, 2020 ), the future trend of GBL ( Giannakas et al, 2018 ; Gao et al, 2020 ), the influencing factors of GBL ( Perttula et al, 2017 ; Shu and Liu, 2019 ), the theoretical foundations of GBL’s effectiveness and its practical use ( Carenys and Moya, 2016 ; Bakan and Bakan, 2018 ; Ab Jalil et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…In this research, 16 relatively high-quality research reviews in the last 5 years have been searched from the major databases in this field (Web of Science, EBSCO ERIC (Education Resources Information Center), IEEE Xplore and SpringerLink). After reviewing these papers, it is found that their main concerns can be summarized into the following four aspects: the effectiveness of GBL ( Meredith, 2016 ; Byun and Joung, 2018 ; Hussein et al, 2019 ; Pellas et al, 2019 ; Tokac et al, 2019 ; Chen et al, 2020 ; Garcia et al, 2020 ; Karakoç et al, 2020 ; Stančin et al, 2020 ), the future trend of GBL ( Giannakas et al, 2018 ; Gao et al, 2020 ), the influencing factors of GBL ( Perttula et al, 2017 ; Shu and Liu, 2019 ), the theoretical foundations of GBL’s effectiveness and its practical use ( Carenys and Moya, 2016 ; Bakan and Bakan, 2018 ; Ab Jalil et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…This research intended to undertake a detailed review of the available literature on students' soft skills to be conducted outbound which makes a positive impact on the personality and behaviour of the management students [94]. The game based learning approach in acquisition of soft skills makes an impact on undergraduate students specifically from software engineering courses [95]. Innovation, and Creativity plays a major role in the psychology of the students which can be developed by motivating students by having activity-based based skills approach [96].…”
Section: Discussionmentioning
confidence: 99%
“…The constant increase of mobile device use, the gamification of education in all levels has led to an increase of student motivation, engagement and achievements throughout their studies, as was pointed out in (Garcia et al, 2020, Hursen et al, 2019, Khaleel at at 2015, O'Connor et al, 2019. Therefore, a new paradigm in distance learning, namely mobile learning, or M-learning, has emerged.…”
Section: System Modelmentioning
confidence: 99%